Mengangkat Kreativitas Dan Daya Saing: Pendampingan Inovasi Desain Kemasan Produk UKM Cirebon - Arif Rinaldi Dikananda; Edi Wahyudin; Siskawati; Tiar Imam Muarif; Nurilah (CV. Multi Kreasi Media, 2022)
Small and Medium Enterprises have an important role in moving the wheels of the economy in Indonesia. Because business management is carried out in a simple and uncomplicated manner, many business actors make SMEs their main choice as business platforms that generate economic value. However, SME products are often underestimated because the packaging is less attractive or does not provide the information that consumers need. The results of assistance activities in Cirebon SME product packaging design innovation, it can be concluded that this effort has succeeded in increasing the creativity and competitiveness of small and medium businesses in Cirebon. This assistance is able to open new insights regarding product packaging design, helping Cirebon SMEs to create a strong and attractive visual identity for consumers. As a result, Cirebon SME products have become more prominent in the market, attracting the interest of more consumers, and strengthening their position in the industry. Apart from that, this activity also strengthens the synergy between Cirebon SMEs. They can share ideas, experiences and knowledge related to packaging design, creating a community that supports each other and motivates each other to continue to innovate. This assistance not only provides benefits in the short term, but also has the potential to have a positive impact in the long term. With attractive packaging designs, Cirebon SME products can expand the market and compete with similar products from other regions. Overall, assistance with product packaging design innovation for Cirebon SMEs has brought significant positive changes for SMEs. This proves that investment in packaging design is an important strategic step to increase competitiveness and advance the SME sector in Cirebon.